The spin-orbit coupling of the 61Σ+ and 43Π states in KCs: Observation and deperturbation. (December 2019) - Szczepkowski, J.; Grochola, A.; Kowalczyk, P.; Jastrzebski, W.; Pazyuk, E.A.; Stolyarov, A.V.; Pashov, A.
Highlights: The energies of 1635 rovibrational levels of the mutually interacting 6 1 Σ + and 4 3 Π electronic states of KCs observed by polarisation labelling spectroscopy. The coupled-channels deperturbation analysis. The ab-initio scalar-relativistic calculation of adiabatic potentials of the interacting states and the spin-orbit coupling matrix element. The results of the deperturbation analysis compared with the theoretical predictions. Abstract: Energies of 1655 rovibrational levels of the mutually perturbed 6 1 Σ + and 4 3 Π 0 + states in KCs were measured in a series of experiments employing polarization labelling spectroscopy technique. The experimental term values of the 6 1 Σ + ∼ 4 3 Π 0 + complex in KCs were used in coupled-channels deperturbation analysis which took explicitly into account the spin-orbit coupling of the 6 1 Σ + and 4 3 Π 0 + states. The empirical deperturbation treatment was supported by ab initio electronic structure calculation of adiabatic potentials of the interacting states and of the corresponding spin-orbit coupling matrix element as a function of internuclear distance.